A Gravity Model Analysis of Irish Merchandise Goods Exports under Brexit - Keogh, Gerard (Statistical and Social Inquiry Society of Ireland, 2019)
This article uses the Gravity Model to explore the effects of Brexit on Irish merchandise goods exports. We embed our approach within the framework of the Structural Gravity Model that incorporates multilateral resistance terms to account for remoteness effects. Further we estimate the parameters of this model using the Poisson Pseudo Maximum Likelihood (PPML) method. Our data source is the Central Statistics Office’s (CSO) 8-digit level CN (Combined Nomenclature) export data covering the years 1994 to 2016. We note that each of these features is novel in the context of modelling Irish exports. Our key findings are a 1% increase in trade costs will result in a fall of 0.73% in goods exports value overall, a value considerably lower in magnitude than has been found previously but nonetheless much more in line with recent international research. A Soft-Brexit where the UK remains within the EU Customs Union will have no effect on the value of trade. Under a Hard Brexit where the UK leaves the Single Market and Customs Union and applies WTO tariffs to Irish goods exports, the value of goods exports to the existing EU-28 will fall by 1.4% while the overall value of goods exports will fall by €0.8bn on average. This overall fall in value will be borne mainly in the traditional sectors of agriculture, food and beverages, and textiles, where the hit will be between 9 to 12% in value terms. In the long term where Irish goods that had been sent to the UK are sent to EU countries instead and sold at EU country market prices, the effect of Brexit will result in a fall of €9.2bn in total export value. Many Irish export firms are unlikely to be able to sustain the associated fall in export sale values of between 50 and 95% and will likely cease trading. In national income terms we also estimate that GNI* will fall by up to 0.4% under WTO tariffs against the current baseline and by over 5%, if over the longer term Irish goods are diverted to other EU countries instead of the UK.
(read before the Society, 6 December 2018)
Keywords: Irish Goods Exports; Brexit; Remoteness Gravity Model; Multilateral Resistance Terms; Poisson Pseudo Maximum Likelihood; GNI (Modified Gross National Income); 314.15